Pengaruh Self-Esteem terhadap College Adjustment terhadap Mahasiswa Baru Pasca Pandemi Covid-19 - Stefani Salma Salsabila Putri; Sulisworo Kusdiyati (UNISBA Press, 2024)
Abstract. On March 11, 2020, the World Health Organization declared the coronavirus disease (COVID-19) outbreak a pandemic. Since then, learning has been carried out online and offline learning will begin in 2021 at the Ministry of Education and Culture, therefore new students need to adapt not only from the transition from high school students to students, but also need to adapt from the online learning system to offline. According to previous research results, college adjustment has several factors that can influence new students' college adjustment to college, one of these factors is self-esteem. College adjustment was measured using the Student Adaptation College Questionnaire (SACQ) by Baker and Syrik (1) and adapted by Zharfa Fitria (2). Meanwhile, Self Esteem is measured using the Rosenberg Self Esteem Scale which has been adapted by Maroqi (3). The method used is quantitative research with a causality research design. The analysis technique used is simple linear regression with a sampling of 314 new students. The sampling technique in this research used convenience sampling. The research results show that self-esteem has a significant influence on college adjustment and the self-esteem variable contributes to the influence on the college adjustment variable by 60.3% based on the R square value obtained. Abstrak. Pada 11 Maret 2020, World Organization Health menyatakan wabah penyakit coronavirus (COVID-19) sebagai pandemi. Semenjak itu, pembelajaran dilakukan online dan pembelajaran offline mulai dilakukan tahun 2021 Kemendikbud, oleh karena itu mahasiswa baru perlu beradaptasi bukan hanya dari transisi dari siswa SMA menjadi mahasiswa, namun perlu beradapatasi dari sistem pembelajaran online menjadi offline. Menurut hasil-hasil penelitian sebelumnya, college adjustment memiliki beberapa faktor yang dapat mempengaruhi college adjustment mahasiswa baru diperguruan tinggi, salah satu faktor tersebut adalah self-esteem. College adjustment diukur menggunakan Alat Ukur Student Adaptation College Quessioner (SACQ) oleh Baker dan Syrik (1) dan diadaptasi oleh Zharfa Fitria (2019). Sedangkan Self esteem diukur menggunakan Rosenberg Self Esteem Scale yang telah diadaptasi oleh Maroqi (3). Metode yang digunakan adalah penelitian kuantitatif dengan desain penelitian kausalitas. Teknik analisis yang digunakan adalah regresi linear sederhanan dengan sampling 314 Mahasiswa baru. Teknik sampling dalam penelitian ini menggunakan convience sampling. Hasil penelitian menunjukan self-esteem secara signifikan memiliki pengaruh terhadap college adjustment dan variable self-esteem memberikan sumbangan pengaruh terhadap variable college adjustment sebesar 60.3% berdasarkan nilai R square yang diperoleh.